Micromarsupialization technique in oral ranula: report of two clinical cases in child patient - Lucas Fernando Oliveira Tomáz Ferraresso; Fábio Anevan Ubiski Fagundes; Mayra Frasson Paiva; Rodrigo Hayashi Sakuma; Cássia Cilene Dezan Garbelini; Farli Aparecida Carrilho Boer (Revista de Odontopediatria Latinoamericana)
Oral ranulas are pseudocysts resulting from the retention of mucus or extravasation of saliva that often affect children. This article aims to report two clinical cases of oral ranulas and discuss the treatment using the micromarsupialization technique. Case 1: 6-year-old girl, attended the Emergency Room of the Bebe Clinic of the State University of Londrina complaining of a “ball under the tongue” lasting approximately 3 months. Clinically, reddish bubble of approximately 1.5 cm in diameter was noted located on the right side of the dome-shaped mouth floor, sessile base and fluctuating. Case 2: 5-year-old girl, attended the same service with a complaint of “bubble on the tongue” lasting approximately 2 months. Clinically, pink-colored bubble similar to the mucosa of approximately 1 cm in diameter was observed located on the left side of the floor of the mouth with a circumscribed shape, sessile base and fluctuating. Based on the clinical aspects and the current history of the lesions, the diagnosis was oral ranula and the surgical treatment performed was micromarsupialization. In a clinical follow-up of 8 and 6 months, respectively, total regression of the lesions was observed, with no clinical signs of recurrence. Based on the reported clinical cases, it can be concluded that the use of micromarsupialization technique represents an effective surgical procedure in children due to its quick execution, conservative approach, without the use of local infiltrative anesthesia, well tolerated and with good prognosis.